The Impact of Covid-19 on the Future of Law - WATNEY, MURDOCH (UJ Press, 2022)
The chapters in this volume focus on the future of law and related disciplines: human rights and access to medical care, corruption and money laundering in state procurement, counterfeit medical products, IPR waiver on COVID-19 vaccines, emergency powers, freedom of expression, prison healthcare, the impact on labour law, access to courts and digital court processes, access to education and the impact on insurance law are but a few possible topics which are addressed.